Lipid Profile in Adolescent Girls with Type 1 Diabetes Mellitus and Hyperandrogenemia - Agnieszka Zachurzok; Grazyna Deja; Aneta Gawlik; Agnieszka Drosdzol-Cop; Katarzyna Klimek; Ewa Malecka-Tendera (International Journal of Endocrinology)
Study Objectives. The study aim was to evaluate whether hyperandrogenemia in adolescent girls with type 1 diabetes mellitus (T1DM) may adversely influence lipid profile. Design and Participants. Lipid levels in 16 diabetic girls with biochemical hyperandrogenemia (T1DM-H) aged 16.3 ± 1.2 years were compared to 38 diabetic girls with normal androgen levels (T1DM-N) aged 15.8 ± 1.2 years. 15 healthy girls served as controls (CG). In all patients, anthropometric measurements were done, and androgens and SHBG were assessed. Results. In T1DM-H, total cholesterol (TC) and low density cholesterol (LDL-ch) were significantly higher than in CG (196.1 ± 41.2 versus 162.7 ± 31.7 mg/dL, p=0.01; 117.3 ± 33.1 versus 91.3 ± 27.8 mg/dL, p=0.01, resp.). Their LDL-ch, non-high density cholesterol (non-HDL-ch) concentrations, and LDL/HDL ratio were also significantly higher than in T1DM-N (117.3 ± 33.1 versus 97.7 ± 26.7 mg/dL, p=0.03; 137.3 ± 42.9 versus 113.3 ± 40.4 mg/dL, p=0.04; 2.8 ± 3.7 versus 1.6 ± 0.5, p=0.04, resp.). In stepwise multiple linear regression, free androgen index (FAI) and waist-to-hip ratio (WHR) were associated with TC (R2=0.4, p<0.0006), non-HDL-ch (R2=0.4, p<0.0003), and LDL-ch (R2=0.4, p<0.0008). Triglycerides and LDL/HDL ratio were (R2=0.7, p<0.0001, R2=0.6, p<0.0003 resp.) related to testosterone, FAI, WHR, and mean HbA1c. Conclusion. Lipid profile in diabetic adolescent girls is adversely influenced by the androgens level, particularly in the group with higher WHR and poorer glycemic control.